PENERJEMAHAN PUISI HEUSCA KEDALAM BAHASA INDONSIA OLEH CHAIRIL ANWAR - ., Nuryadi (Fakultas Komunikasi, Sastra, dan Bahasa, 2012)
This paper discusses English-poetry translation, Heusca by John Conford into Indonesian translated by Chairil Anwar. The purpose of this study is to determine how the translator considers aesthetic and expressive values from the source language and translate them into target language. Aesthetic values are the means of delivery thought through the use of poetic language such as diction or word choice, metaphor, imageri, and others figurative language. Meanwhile, the expressive values are the means of delivery thoughts through the author's mind or emotions such as structure, rhyme, and pronunciation. The method used in this study is a qualitative descriptive analysis of the meaning. The results of analysis show that in terms of meaning, aesthetic values, and structures, Heusca is the result of a semantic translation and faithful to source language. Translator managed to retain the meaning of source language. In other word, the translation can meet the requirements of fidelity. In terms of expressive values in particular aspects of meter and rhyme are not so faithful to source language because the source language and the target language have some differences. Basically, this is acceptable that the Indonesian language as target language has a very big difference in terms of pronunciation with English as the source language. As a result, meter and rhyme of target language may not be forced into the source language without damaging the naturalness of meaning for target language readers. It can be said that the translation can meet the transparency criteria because source language appeared in poetry comes naturally to native speakers of English.